The determinants of liquidity risk: a panel study of Islamic Banks in Malaysia - Yaacob Abdul Karim, Abdul Rahman Aisyah, Abdul Karim Zulkefly, (Universiti Pendidikan Sultan Idris, 2016)
The determinants of liquidity risk: a panel study of Islamic Banks in Malaysia by Yaacob Abdul Karim, Abdul Rahman Aisyah, Abdul Karim Zulkefly,